Molecular fingerprints resolve affinities of Rhynie chert organic fossils - C. C. Loron; E. Rodriguez Dzul; P. J. Orr; A. V. Gromov; N. C. Fraser; S. McMahon (Nature Communications, 2023)
It can be challenging to identify extinct organisms with morphology alone. Here, the authors use non-destructive Fourier Transform Infrared Spectroscopy to determine the molecular fingerprints of eukaryotes and prokaryotes from the 407 Ma Rhynie chert fossil assemblage of Aberdeenshire, Scotland.